THE INFLUENCE OF BEAUTY INFLUENCER MARKETING AND POSITIVE ELECTRONIC WORD OF MOUTH (E-WOM) ON KOREAN SKINCARE BRAND PURCHASE DECISIONS MEDIATED BY BRAND TRUST - Adinda Septi Utami; Baiq Handayani Rinuastuti; Lalu Edy Herman Mulyono (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence of Beauty Influencer Marketing and Positive Electronic Word of Mouth (E-WOM) on purchasing decisions for Korean skincare brand products, both directly and indirectly through Brand Trust as a mediating variable. The research method uses a quantitative approach by distributing questionnaires to 129 respondents who are users of Korean skincare brands. Data were analyzed using Partial Least Square (PLS). The results show that Beauty Influencer Marketing and Positive E-WOM do not have a direct effect on purchasing decisions, but both have a significant effect on Brand Trust. In addition, Brand Trust is proven to have a positive effect on purchasing decisions, as well as mediating the influence of Beauty Influencer Marketing and Positive E-WOM on purchasing decisions. These findings confirm that the role of brand trust is very important in encouraging consumers to make purchases, especially for imported skincare products that are classified as high involvement.